Fludarabine Inhibits KV1.3 Currents in Human B Lymphocytes - de la Cruz, Alicia; Vera-Zambrano, Alba; Peraza, Diego A.; Valenzuela, Carmen; Zapata, Juan M.; Perez-Chacon, Gema; Gonzalez, Teresa (Frontiers in Pharmacology, 2017)
Fludarabine (F-ara-A) is a purine analogue commonly used in the treatment of indolent B cell malignancies that interferes with different aspects of DNA and RNA synthesis. Kv1.3 K+ channels are membrane proteins involved in the maintenance of K+ homeostasis and the resting potential of the cell, thus controlling signaling events, proliferation and apoptosis in lymphocytes. Here we show that F-ara-A inhibits Kv currents in human B lymphocytes. Our data indicate that Kv1.3 is expressed in both BL2 and Dana B cell lines, although total Kv1.3 levels were higher in BL2 than in Dana cells. However, Kv currents in the plasma membrane were similar in both cell lines and were abrogated by the specific Kv1.3 channel inhibitor PAP-1, indicating that Kv1.3 accounts for most of the Kv currents in these cell lines. F-ara-A, at a concentration (3.5 µM) similar to that achieved in the plasma of fludarabine phosphate-treated patients (3 µM), inhibited Kv1.3 currents by 61±6.3% and 52.3±6.3% in BL2 and Dana B cells, respectively. The inhibitory effect of F-ara-A was concentration-dependent and showed an IC50 value of 0.36±0.04 µM and a nH value of 1.07±0.15 in BL2 cells and 0.34±0.13 µM (IC50) and 0.77±0.11 (nH) in Dana cells. F-ara-A inhibition of plasma membrane Kv1.3 was observed irrespective of its cytotoxic effect on the cells, BL2 cells being sensitive and Dana cells resistant to F-ara-A cytotoxicity. Interestingly, PAP-1, at concentrations as high as 10 µM, did not affect the viability of BL2 and Dana cells, indicating that blockage of Kv1.3 in these cells is not toxic. Finally, F-ara-A had no effect on ectopically expressed Kv1.3 channels, suggesting an indirect mechanism of current inhibition. In summary, our results describe the inhibitory effect of F-ara-A on the activity of Kv1.3 channel. Although Kv1.3 inhibition is not sufficient to induce cell death, further research is needed to determine whether it might still contribute to F-ara-A cytotoxicity in sensitive cells or be accountable for some of the clinical side effects of the drug.